PROPOSTAS DE MELHORIA PARA A SUPERVISÃO METROLÓGICA BASEADAS NAS PERCEPÇÕES DO SETOR ELÉTRICO DO BRASIL - Timmins, Aline de Souza Pinto (2011)
The aim of this dissertation is to evaluate and propose improvements to the activities related to Metrological Supervision, applied to the electric power sector. Currently this activity is managed by the Inmetro s Legal Metrology Directory, and applied to manufacturers of water, gas and electricity meters, to utilities that provide these three services and recently to sphygmomanometers and chronotachographs manufacturers throughout Brazil. The study got its start by identifying the problem, which deals with the difficulty of effective service to the demand for authorization for initial verification and Authorized Testing Station for that sector. After identifying the problem, we defined the main objective to be achieved by relating it to intermediate goals, or to propose improvements to the activity it was necessary to map and identify its critical steps, and then develop and implement a questionnaire with a set of tips for evaluating the perception of power sector experts and officials of Inmetro s Legal Metrology Directory. Proposals such as the creation of a guidance document to facilitate understanding of legislation governing the activity, assessment of ability to perform tests of the companies already authorized to perform verification during the Technical Type Approval in order to expedite the expansion of scope, as well as training new teams of auditors to perform an activity under supervision of Legal Metrology Directory, emerged from the convergence of research questions among the groups surveyed. The results indicate the need to restructure in order to respond to requests from authorized testing stations and manufacturers allowed to perform initial verification tests to ensure the effectiveness of the whole process and therefore better serve the needs of society.